Emotional, informational and instrumental support needs in patients with breast cancer who have undergone surgery: a cross-sectional study - Tingting Cai; Qingmei Huang; Changrong Yuan (BMJ Open)
Objectives This study evaluated emotional, informational and instrumental support needs in patients with breast cancer who had undergone surgery, then identified the variables associated with those needs.Design This was a cross-sectional survey study.Setting Questionnaires were distributed in tertiary hospitals in China between January 2018 and July 2020.Participants We recruited 477 eligible patients with breast cancer via convenience sampling. Due to exclusions for response errors, the final analysed sample included 461 participants (mean age of 50.9 years). Each completed a questionnaire consisting of a sociodemographic information component and three short forms from the Patient-Reported Outcome Measurement Information System (social relationships short forms, anxiety short form and depression short form). Subsequent analyses included the χ2 test, Pearson correlation and multivariate regression.Results The T scores for informational support were lower than those for the reference group (general population), while those for emotional and informational support were average. Marital status, childbearing history, lifestyle, employment status, anxiety and depression levels were related to the scores for emotional, informational and instrumental support in this population. The regression analysis revealed that emotional support levels, instrumental support levels, marital status, employment status, anxiety and depression outcomes were predictors for informational support levels.Conclusions Informational support should be specifically assessed and promoted among patients with breast cancer in general, while marital status, childbearing history, lifestyle, employment status, anxiety and depression levels should be evaluated when conducting interventions to promote emotional, informational and instrumental support for those who have undergone surgery. Early and regular screenings for high-risk patients will help nurses identify those who are likely to benefit from targeted preventive interventions aimed at emotional, informational and instrumental support issues.Trial registration number ChiCTR2000035439; ClinicalTrials.gov registry.